Sugar Works, Shawnee County - Todd, Danielle (Kansas State University, The Chapman Center for Rural Studies, 2011)
In the late nineteenth century there was a passion for growth and development among Americans. Their dream was to own land and strike gold. In the case of many early Kansans, the gold would come from a sweet treat, sugar, processed from sugar beets grown in the rich Kansas soils. Their economic dreams concentrated in an area outside of Topeka, Kansas, called Sugar Works. This ghost town came and went quickly but its story of hope and dreams for wealth will live on.
Danielle Todd, “Sugar Works, Shawnee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/55.
Keywords: Kansas River; National Sugar Company of Boston; Shawnee County; Sugar Works; Tecumseh Township; Topeka